STRUKTUR PASAR DAN PERILAKU KOMPETITIF INDUSTRI PERBANKAN INDONESIA PASCA IMPLEMENTASI API 2004 - Malik, Nazaruddin (Faculty of Economics and Business, University of Muhammadiyah Malang, 2010)
This study aims to explain the market structure and competitive behavior of the Indonesian banking. Found that the market structure group of large banks declined from oligopoly leads to monopoly. In a large group of medium-small banking moving toward behavior monoplistik competition. Variation of the management efficiency of input factors, production capacity and business mix impact on variations in interest income and income distribution is unequal total inter-bank or bank group. Post-entry into the API, intense competition, the actions need to be followed closely and carefully by the bank management, but that does not mean reduction in financing opportunities in the banking sector that minimal risk